TANGGUNG JAWAB SOSIAL (CSR), IMBAL HASIL ATAS EKUITAS (ROE), DAN REPUTASI PERUSAHAAN: (CORPORATE SOCIAL RESPONSIBILITY, RETURN ON EQUITY, AND CORPORATE REPUTATION) - Ramdani, Hendi; Animah, Animah (UPT Penerbitan Universitas Jember, 2024)
This research aims to evaluate the influence of CSR and ROE on the reputation of manufacturing companies listed on the IDX. This research uses a quantitative approach with a sampling of 25 manufacturing companies listed on the IDX during the 2018-2022 period. The sampling technique used is purposive sampling, where reputable companies are taken as samples. CSR, ROE and corporate reputation data were collected from annual reports and official IDX publications. Linear regression analysis is used to test the relationship between these variables. The research results show that both CSR and ROE have a significant influence on the reputation of manufacturing companies listed on the IDX. The regression coefficients for CSR and ROE show that every one unit increase in CSR and ROE causes a significant increase in corporate reputation. These findings have important implications for business and management practitioners at BEI. Improving CSR practices and financial performance can help companies strengthen their reputation in the eyes of Stakeholders. A better understanding of the relationship between CSR, ROE, and corporate reputation can also help companies design more effective business strategies.